Price Discovery on Stock Index Futures markets under Extreme Events: Evidence from China - Zhang, Qian (European Scientific Journal, ESJ, 2018)
In this paper, the price discovery function of stock index futures for spot stock index is studied in view of the soaring and plunging periods of Chinese stock market in recent years. We use the VECM model to do empirical research under periods of stationary, boom and slump. The results show that there is a long-term relationship between CSI 300 index and CSI 300 index futures. During the stable period of Chinese stock market, the CSI 300 stock index futures are sensitive to the short-term impact, and its ability of price discovery is obviously. However, during the period of boom and collapse, the price discovery function of CSI 300 index futures is weak.